Colombian anopheles triannulatus (diptera: culicidae) naturally infected with plasmodium spp. (2013)
ABSTRACT : The role of Anopheles triannulatus as a local vector has not yet been defined for malaria-endemic regions of Colombia.Therefore, the aimof this work was to detect An. triannulatus naturally infected with Plasmodiumspp., as an approximation to determining its importance as malaria vector in the country. A total of 510 An. triannulatus were collected in six malaria-endemic localities ofNW and SE Colombia from January 2009 to March 2011. In the NW, two specimens were naturally infected; one with Plasmodium vivax VK247, collected biting on humans and the other with Plasmodium falciparum, collected resting on cattle. In the SE, two specimens were positive for P. falciparum. Although these results show An. triannulatus naturally infected with Plasmodium, further studies are recommended to demonstrate the epidemiological importance of this species in malaria-endemic regions of Colombia.